Prevalence, incidence, and clinical impact of sarcopenia: facts, numbers, and epidemiology—update 2014. Issue 4 (22nd October 2014) - Morley, John E.; Anker, Stefan D.; von Haehling, Stephan
Abstract : Sarcopenia is now defined as a decline in walking speed or grip strength associated with low muscle mass. Sarcopenia leads to loss of mobility and function, falls, and mortality. Sarcopenia is a major cause of frailty, but either condition can occur without the other being present. Sarcopenia is present in about 5 to 10 % of persons over 65 years of age. It has multiple causes including disease, decreased caloric intake, poor blood flow to muscle, mitochondrial dysfunction, a decline in anabolic hormones, and an increase in proinflammatory cytokines. Basic therapy includes resistance exercise and protein and vitamin D supplementation. There is now a simple screening test available for sarcopenia—SARC‐F. All persons 60 years and older should be screened for sarcopenia and treated when appropriate.